2021
DOI: 10.1038/s41598-021-96500-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of face masks on interpersonal trust in times of COVID-19

Abstract: Despite the widespread use of face masks to combat COVID-19, little is known about their social and behavioral consequences. To understand the impact of face masks on interpersonal trust, we designed a novel experiment to assess the causal impact of face mask use on whether individuals follow economically relevant advice from a stranger. From a survey of more than 2000 US citizens, conducted during July and August 2020, we find that almost 5% fewer individuals trust advice when it is given by someone wearing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…In contrast, other studies have highlighted a negative bias in trustworthiness appraisals of masked faces. For example, Malik et al (2021) showed videos of masked or unmasked actors offering economical advice to more than 2000 US citizens and found that only 5% trusted the advice given by masked strangers than when it was given by the unmasked strangers. In a rating study by Biermann et al (2021) , masked faces were evaluated as less trustworthy and less happy than unmasked faces; however, this effect was attenuated in participants who experienced high psychological distress and risk perception associated with the pandemic, and who showed high compliance with prevention measures to avoid infection.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies have highlighted a negative bias in trustworthiness appraisals of masked faces. For example, Malik et al (2021) showed videos of masked or unmasked actors offering economical advice to more than 2000 US citizens and found that only 5% trusted the advice given by masked strangers than when it was given by the unmasked strangers. In a rating study by Biermann et al (2021) , masked faces were evaluated as less trustworthy and less happy than unmasked faces; however, this effect was attenuated in participants who experienced high psychological distress and risk perception associated with the pandemic, and who showed high compliance with prevention measures to avoid infection.…”
Section: Introductionmentioning
confidence: 99%
“…What modulates statements’ credibility instead are facemasks. Extant studies focus on either explicit judgments or implicit measures of trustworthiness impressions from masked faces (Cartaud et al, 2020 ; Olivera-La Rosa et al, 2020 ; Biermann et al, 2021 ; Grundmann et al, 2021 ; Malik et al, 2021 ; Marini et al, 2021 ; Oldmeadow & Koch, 2021 ) have highlighted two ways in which masks can act upon the trustworthiness impression of a face who don it. First, the very presence of a facemask can enhance trustworthiness impression, arguably due to signaling care for others (Cartaud et al, 2020 ; Marini et al, 2021 ; Olivera-La Rosa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the very presence of a facemask can enhance trustworthiness impression, arguably due to signaling care for others (Cartaud et al, 2020 ; Marini et al, 2021 ; Olivera-La Rosa et al, 2020 ). In some cases, facemasks have also been reported to decrease trustworthiness impression, likely due to their association with the harm brought about by the Covid-19 pandemic (Biermann et al, 2021 ; Malik et al, 2021 ). In both cases, however, the effect is due to the meaning assigned to the mask itself rather than on its effect on the underlying face.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations